Pragmatic force modifiers in English-medium master's thesis defenses in Taiwan universities. (April 2020) - Lin, Chia-Yen
Abstract: This corpus-based study uses quantitative and qualitative methods to analyze pragmatic force modifiers (PFMs) in seven English-medium Master's thesis defenses from four Taiwan universities. The study reveals a broad distribution of modifiers in the defense corpus, which adds to the research on the commonality of linguistic features in various academic genres and implies that academic discourse norms play a greater role than linguistic/cultural conventions in their widespread prevalence. Striking similarities in the type and frequency of the modifiers of the committee and candidate sub-corpora suggest their functions as effective rhetorical elements, and that they are used by both groups to co-structure institutionally accredited defense discourses, secure original contributions to disciplinary knowledge, and denote the acculturation of new members to the academic community. However, significant differences occur, which can be attributed to the influence of institutional duties, dynamic roles, and communicative aims in distinct interaction patterns. Role fluidity is largely a manifestation of the enhanced resourcefulness of committees in helping candidates succeed in the high-stakes event. These findings have considerable significance for awareness-raising and linguistic training activities designed to prepare students for English-medium oral defenses. Highlights: High frequencies of pragmatic force modifiers are found in Taiwanese thesis defenses. Functions of modifiers contribute to the co-construction of defense discourse. Homogeneity confirms similar use in Anglophone and the present academic communities. Differences in frequency and function are linked to committees and candidates. Role fluidity is a manifestation of ELF committees' enhanced resourcefulness.